Delayed Initiation of Calcineurin Inhibitor Is Critical for Tolerance Induction By Posttransplant Cyclophosphamide - Senjo, Hajime; Hashimoto, Daigo; Okada, Satomi; Kubota, Shimpei I; Ito, Ayumu; Tanaka, Takashi; Saito, Yumika; Miyajima, Toru; Li, Wenyu; Zhang, Zixuan; Harada, Shinpei; Hasegawa, Yuta; et al. (Blood, 2023)
[Introduction] We have previously shown that T-cell exhaustion of donor alloreactive T cells plays a critical role in tolerance induction after mouse allogeneic hematopoietic cell transplantation (allo-HCT) (Asakura S: JCI 2010). Emerging evidence indicates that T-cell exhaustion is a multistep process, including precursors of exhausted T cells (pTex) with stem cell-like properties, pTex-derived transitory exhausted T cells (transitory-Tex) with potent effector-like functions, and terminally exhausted T cells (terminal-Tex) with the expression of multiple inhibitory receptors and severely impaired functions. We have demonstrated, for the first time, that calcineurin inhibitors (CNIs) inhibit tolerance induction by suppressing the terminal exhaustion of donor T cells while inducing transitory-Tex after allo-HCT in mice (Senjo H: Blood 2023). In contrast, post-transplantation cyclophosphamide (PTCy) efficiently induces tolerance with low incidence of chronic GVHD. In the current study, we evaluated the mechanisms by which PTCy could induce tolerance even with the use of CNIs. [Methods] In mouse haploidentical HCT model,B6D2F1 recipients (H-2 b/d) were lethally irradiated and transplanted with 2 × 10 6 T cells together with T-cell-depleted bone marrow cells from C57BL/6 (H-2 b) donors on day 0. CSP (25 mg/kg) was administered from either day 0 (early-CSP) or day 5 (late-CSP), and PTCy (50 mg/kg) was i.p. injected on day 3 after HCT. In clinical study, peripheral blood mononuclear cells were prospectively collected from patients who underwent PTCy-based haplo-PBSCT at our institutions after approval of institutional review. [Results] We have shown that Ly6C is a specific marker for transitory-Tex in mice (Senjo H: Blood 2023). In mice, early-CSP followed by PTCy (CSP→PTCy) significantly expanded Ly6C +PD-1 +TOX low CD8 + T cells and Ly6C +PD-1 +GZMB + CD4 + T cells on day 14, while late-CSP following PTCy (PTCy→CSP) induced T-cell differentiation towards Ly6C -PD-1 +TOX high terminally exhausted T cells. When CSP→PTCy recipients were injected with anti-PD-L1 monoclonal antibodies, transitory-Tex demonstrated vigorous proliferation, while terminal-Tex did not respond to PD-1 blockade. These findings indicate that CSP administration after PTCy promotes tolerance induction, whereas CSP administered before PTCy inhibits tolerance induction. Next, we explored the specific markers for human transitory-Tex using scRNA-seq of T cells from the patients who underwent PTCy haplo-PBSCT, in which tacrolimus (TAC) was started either from day -1 (early-TAC) or day 5 (late-TAC). UMAP analysis showed that early-TAC expanded cluster 5 (C5) out of six CD8 + clusters (C1-C6) and C8 out of three CD4 + clusters (C7-C9) (Fig.1). C5 highly expressed exhaustion markers such as Tox and Pdcd1, together with effector molecules such as Prf1, Gzmb and Cx3cr1, while C8 was characterized with high expression of Gzmb, indicating that C5 and C8 are the human counterparts of transitory-Tex. Analysis of differentially expressed genes showed that Fcgr3a (CD16A) was selectively expressed in C5, while Gzmb and Cd74 were selectively expressed in C8. These two populations showed robust proliferative responses to TCR stimulation in vitro. ScTCR-seq demonstrated that C5 and C8 clusters showed less TCR diversity compared to other clusters, suggesting that C5 and C8 were enriched with alloreactive donor T cells that clonally expanded post-transplant. FCM confirmed that both CX3CR1 +CD16 + CD8 + T cells and GZMB +CD74 +CD4 + T cells were significantly increased in the early-TAC group compared to the late-TAC group on day 28 (Fig. 2). In the early-TAC group, 2/9 patients developed moderate and severe chronic GVHD, and only 1/9 patient was off-immunosuppressants (Fig 2). In sharp contrasts, in the late-TAC group, no patient developed chronic GVHD, and 7/9 patients were off-immunosuppressants. Importantly, two patients who developed chronic GVHD had a particularly high proportions of CX3CR1 +CD16 +CD8 + and GZMB +CD74 +CD4 + transitory-Tex on day 28 after HCT (Fig.2). [Conclusion] Our study demonstrated that early initiation of CNIs before PTCy induced transitory-Tex and inhibited tolerance induction after PTCy haplo-PBSCT. Administration of CNIs after PTCy is critical for tolerance reduction without chronic GVHD. Hashimoto:Daiichi Sankyo Inc: Honoraria; Astellas Pharma: Honoraria; LUCA Science: Patents & Royalties; Kyowa Kirin: Honoraria; Ono Pharma: Honoraria; Janssen Pharma: Honoraria; Chugai Pharmaceutical: Honoraria. Inamoto:Novartis: Honoraria; Janssen: Honoraria; Meiji Seika Pharma: Honoraria, Research Funding; Amgen: Research Funding. Teshima:Chugai: Honoraria, Research Funding; Janssen: Honoraria, Membership on an entity's Board of Directors or advisory committees; Priothera SAS: Research Funding; Merck Sharp & Dohme: Honoraria; Bristol-Myers Squibb: Honoraria; LUCA Science: Research Funding; Fuji Pharma: Research Funding; AbbVie: Honoraria; Asahi Kasei Pharma: Membership on an entity's Board of Directors or advisory committees, Research Funding; Sumitomo Pharma: Honoraria, Membership on an entity's Board of Directors or advisory committees, Research Funding; ONO: Research Funding; Astellas: Honoraria, Membership on an entity's Board of Directors or advisory committees, Research Funding; SHIONOGI: Research Funding; Otsuka: Research Funding; Novartis: Honoraria, Membership on an entity's Board of Directors or advisory committees; Celgene: Honoraria, Membership on an entity's Board of Directors or advisory committees; DAIICHI SANKYO: Membership on an entity's Board of Directors or advisory committees; AstraZeneca: Membership on an entity's Board of Directors or advisory committees; Takeda: Membership on an entity's Board of Directors or advisory committees; Roche Diagnostics: Membership on an entity's Board of Directors or advisory committees; Sanofi: Membership on an entity's Board of Directors or advisory committees; Meiji Seika Pharma: Membership on an entity's Board of Directors or advisory committees; Eisai: Research Funding; NIPPON SHINYAKU: Honoraria, Research Funding; Kyowa Kirin: Honoraria, Research Funding. [Display omitted]